High Remission Rates in a Brazilian Cohort of Initial Rheumatoid Arthritis after 15 Years of Follow-Up - Heller, Heloisa Lima; Reis, Ana Paula Gomides; Albuquerque, Cleandro; Jochims, Isadora; Mota, Licia; Muniz, Luciana; Yokoy, Talita (My University, 2021)
Introduction: Rheumatoid arthritis (RA) is a chronic systemic rheumatic disease which is usually treated with corticosteroids and immunobiologicals. The goal of this article is to carry out an assessment of disease activity indices in a cohort of patients with rheumatoid arthritis. Patients and Methods: This is a prospective cohort study. Individuals from the Initial Rheumatoid Arthritis Brasília Cohort, which is an incident cohort of early RA diagnosed patients, were monitored at the Rheumatology Service of the Hospital Universitário de Brasília (HUB), University of Brasília (UnB), Brazil. A cross-sectional analysis was carried out from 2017 to 2018 to evaluate patients with 15 or more years of follow-up, through a direct interview and review of medical records. The main focus of the study is on the assessment of disease activity, based on the indices: 28-joint Disease Activity Score based on C-reactive protein (DAS 28 CPR) and based on erythrocyte sedimentation rate (DAS 28 ESR), Clinical Disease Activity Index (CDAI), and Simple Disease Activity Index (SDAI). The reference remission criteria used were the Composite Disease Activity Indices. Results: 107 patients were evaluated, mostly women, mean age of 55.1 years. Concerning the disease characteristics, 75.5% of the patients were positive for rheumatoid factor and 12 (11.3%) had documented erosive disease. The mean Health Assessment Questionnaire (HAQ) at the time of assessment was 0.6 (median 0.35). The indices analyzed showed: DAS28-ESR 48.6% of patients were in remission and 12.1% had low activity levels, DAS28-CRP 55.1% and 11.2%, SDAI 42% and 26.1%, CDAI 41.1% and 27.1%. These remission and low disease activity levels are higher than those generally found in the literature. Conclusion: This study presents a cohort of patients with RA who started treatment at an early stage of the disease and who achieved higher rates of remission and lower disease activity than those reported in the literature. Keywords Rheumatoid Arthritis, Remission Induction, Therapeutics
Keywords: Artrite reumatóide; Indução de remissão; Terapêutica